Implementation of PID Controller on Hohenheim Tunnel Dryer Using Ziegler-Nichols Approach Method - Melinda Melinda; Rita Khatir; Ari Rahmat Putra Ibina; Alfatirta Mufti; Rizal Syahyadi; Iskandar Hasanuddin (Jurnal POLIMESIN, 2023)
Hohenheim Tunnel Dryer has two heating mechanisms, namely the solar collectors and the greenhouse effect. Two outlet fans are used to remove moisture from drying as well as to lower the temperature in the drying chamber. Suppose the outlet fans are turned on continuously, the temperature in the drying room will not reach the optimal drying temperature, and vice versa if the outlet fans are not turned on, the drying temperature can exceed 60°C. Controlling these outlet fans manually is a very inconvenient thing and becomes an obstacle for accepting this drying technology by the farmers. Therefore, this study focused on the design of temperature control for the Hohenheim Tunnel Dryer by using a proportional integral derivative (PID) controller with an Arduino Nano microcontroller. It controls the fan outlet to obtain an optimal drying temperature so that the operation of this dryer becomes more accessible and more efficient. The temperature sensor used is DHT22. The tuning method chosen is the Ziegler – Nichols method, and the setpoint value is selected at 55, which is the optimum temperature for drying most agricultural products. The design, manufacture, and testing of the temperature control system on the Hohenheim tunnel dryer was successfully carried out without over shoot and steady state error so it can be concluded that the system has worked well.